Doña Flor : a tall tale about a giant woman with a great big heart - Mora, Pat (Knopf, 2005)
Doña Flor, a giant lady with a big heart, sets off to protect her neighbors from what they think is a dangerous animal, but soon discovers the tiny secret behind the huge noise.